2015
DOI: 10.1002/ejoc.201403452
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Pyridylphosphonates by Rhodium‐Catalyzed [2+2+2] Cycloaddition of 1,6‐ and 1,7‐Diynes with Diethyl Phosphorocyanidate

Abstract: The convenient and atom‐economical synthesis of substituted bicyclic pyridylphosphonates has been achieved by the cationic rhodium(I)/H8‐binap‐complex‐catalyzed [2+2+2] cycloaddition of 1,6‐ and 1,7‐diynes with diethyl phosphorocyanidate. These reactions may proceed via an azarhodacyclopentadiene intermediate in addition to the rhodacyclopentadiene intermediate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 103 publications
0
6
0
Order By: Relevance
“…utilizing feedstock chemicals as starting materials to build diverse substitution patterns in a single synthetic step. [27][28][29][30][31][32][33][34] Correspondingly, an asymmetric catalytic version to assemble enantioenriched pyridines is a conceptually straightforward yet largely unsolved route. 35 There are a handful of examples reported but primarily limited to the construction of atropisomers of arylpyridines (Scheme 1D).…”
Section: The Bigger Picturementioning
confidence: 99%
“…utilizing feedstock chemicals as starting materials to build diverse substitution patterns in a single synthetic step. [27][28][29][30][31][32][33][34] Correspondingly, an asymmetric catalytic version to assemble enantioenriched pyridines is a conceptually straightforward yet largely unsolved route. 35 There are a handful of examples reported but primarily limited to the construction of atropisomers of arylpyridines (Scheme 1D).…”
Section: The Bigger Picturementioning
confidence: 99%
“…58 The authors also reported an example of pyrrolidine-fused pyridine 80 preparation from 9a and diethyl phosphorocyanidate 79 (Scheme 28c). 59 Recently, Wan and co-workers described a general and efficient synthesis of 4,6,7-trisubstituted 2,3-dihydro-1H-pyrrolo [3,4-c]pyridines 83 by the [2 + 2 + 2] cycloaddition of corresponding dipropargyl amines 81 with ethyl 2-(hydroxyimino) acetate 82 employing a Rh(NBD) 2 BF 4 /MeO-biphep combination as the catalytic system in reuxing ethanol. This process tolerated various sensitive functional groups and generally provided 83 in good to excellent yields (Scheme 29).…”
Section: Isoindoline Derivatives From Nitrogen-linked 16-diyenes Andmentioning
confidence: 99%
“…14 Furthermore, an efficient method for the synthesis of azatriphenylene derivatives through transition metal-catalyzed [2 + 2 + 2] cycloadditions of biaryl-linked diynes with nitriles was developed by the groups of Deiters 12 b and Tanaka. 15 Subsequently, photochemical cyclodehydrochlorination was used to produce azatriphenylene derivatives by the groups of Morin 16 a and Alabugin. 16 b In 2020, Zhao and coworkers synthesized azatriphenylene derivatives by double Suzuki coupling followed by the Scholl reaction.…”
Section: Introductionmentioning
confidence: 99%